(untitled) (ACME, 2024)
The investigation aims at analysing the two general notions of mankind and people in two lexicographic reference works on trade and commerce published in London in the 1750s: Rolt’s A New Dictionary of Trade and Commerce (1756) and Postlethwayt’s The Universal Dictionary of Trade and Commerce (1757). An overview of the same notions in universal dictionaries of arts and sciences (cfr. References, Primary Sources), issued before and after ND and UD, will also be of help to define a more general background. Starting from the key words mankind and people, their frequency and relevance in the two dictionaries, the investigation is widened to include related terms (e.g. multiword expressions and language patterns in which mankind and people occur) and semantic categories (e.g. specific contexts of use: social condition, social values, demography, identity and citizenship, etc.). The many entries, cross-references, and the various lexical clusters reveal a complex lexicographic and lexicological network. This network, beyond providing information and contents on specific topics, ultimately emphasises the hierarchical organising principle at the basis of Late Modern British society: in particular, people unfolds into a myriad of ‘entities’. Dictionaries of trade and commerce are plentiful sources of knowledge, from general concepts and notions to more specific contents, but also powerful ideological tools.